2013
DOI: 10.3791/50379
|View full text |Cite
|
Sign up to set email alerts
|

Free Radicals in Chemical Biology: from Chemical Behavior to Biomarker Development

Abstract: The involvement of free radicals in life sciences has constantly increased with time and has been connected to several physiological and pathological processes. This subject embraces diverse scientific areas, spanning from physical, biological and bioorganic chemistry to biology and medicine, with applications to the amelioration of quality of life, health and aging. Multidisciplinary skills are required for the full investigation of the many facets of radical processes in the biological environment and chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Synthesis of mono-trans isomers of CholLin ( 5 ) and mono-trans isomers of CholAra ( 6 ) were based upon the procedure described in our previous work. 28,29 For the synthesis of cholesteryl elaidate ( 4 ; CholEla; 9t-18:1), see Supplemental Material.…”
Section: Methodsmentioning
confidence: 99%
“…Synthesis of mono-trans isomers of CholLin ( 5 ) and mono-trans isomers of CholAra ( 6 ) were based upon the procedure described in our previous work. 28,29 For the synthesis of cholesteryl elaidate ( 4 ; CholEla; 9t-18:1), see Supplemental Material.…”
Section: Methodsmentioning
confidence: 99%
“…ROS are constantly produced as part of normal cellular metabolic processes (such as cellular respiration, antibacterial defense) and external exposures (such ionizing radiation, smoking, and toxins) as discussed earlier [46,47]. Increased oxidative stress can arise from higher rates of ROS generation compared to its removal rates [15,17].…”
Section: Oxidative Stress and Afmentioning
confidence: 99%
“…Different studies have demonstrated that several biomarkers such as NOXs and MPO predict the risk of AF and morbidity and mortality in AF patients [50,73]. A recent prospective cohort study found that 8-iso-PGF2α levels predict cardiovascular events and total mortality [47]. Several studies have assessed the predictive values of urinary biomarkers of oxidative stress in the context of AF, which are summarized in Table 1 [29, 51, 57, 74 -76].…”
Section: Af Vs Non-af: Cross-sectional and Prospective Studiesmentioning
confidence: 99%
“…Future studies, in association with multidisciplinary technological approaches will help in discovery of new biomarkers. Aiming to connect free radical chemical reactivity with biological processes, Chatgilialoglu et al [ 120 ], developed a chemical biology approach to provide information on the mechanistic pathways and products. The core of this approach was the design of biomimetic models to study biomolecule behavior, including lipids, nucleic acids and proteins, in aqueous systems especially under conditions of physiological oxidative stress mimicking the in vivo situation.…”
Section: Lipid Peroxidation Biomarkers In Carcinogenesismentioning
confidence: 99%
“…The core of this approach was the design of biomimetic models to study biomolecule behavior, including lipids, nucleic acids and proteins, in aqueous systems especially under conditions of physiological oxidative stress mimicking the in vivo situation. By this way we can obtain insights of the reaction pathways as well as building up molecular libraries of the free radical reaction products [ 120 ].…”
Section: Lipid Peroxidation Biomarkers In Carcinogenesismentioning
confidence: 99%